Comparison of the Victorian Audit of Surgical Mortality with coronial cause of death. Issue 6 (28th May 2015) - Hansen, Dylan; Retegan, Claudia; Woodford, Noel; Vinluan, Jessele; Beiles, Charles B.
Abstract: Background: The Victorian Audit of Surgical Mortality (VASM) is designed to improve the level of patient care by educating surgeons of areas for improvement in patient management during a surgical admission. Coronial data obtained via the National Coronial Information System were used as an independent method to validate the cause of death as determined by the treating surgeon. Method: The audit prospectively collected 4905 cases that underwent peer assessment and 842 (17%) received an in‐depth second‐line assessment of which 200 (24%) also underwent a coronial review. Using the coronial assessment as the reference standard, retrospective comparison of coronial diagnoses compared with the audit case outcomes was conducted to determine the overall accuracy of the stated cause of death. The degree of agreement was also analysed based on whether the patient received a full autopsy (internal examination) or an external examination only. The time taken to obtain the coronial and audit case closure was also analysed. Results: Overall, 195 of the 200 cases had a cause of death identified by the coroner. In 82%, the cause of death reported to VASM by the treating surgeon matched the cause of death determined by the coroner. Concordance was not affected by the extent of post‐mortem performed. Time taken to finalize cases was slightly shorter for the coronial process, but unclosed coronial findings resulted in the exclusion of 103 cases. Conclusion: The causes of death data in VASM are accurate when compared with the coronial data independent of whether the coronial investigation included a complete autopsy.